Transcriptomic alterations in the sweet orange vasculature correlate with growth repression induced by a variant of citrus tristeza virus - Aknadibossian, Vicken; Huguet-Tapia, Jose C.; Golyaev, Victor; Pooggin, Mikhail M.; Folimonova, Svetlana Y. (Frontiers in Microbiology, 2023)
Citrus tristeza virus (CTV, family Closteroviridae) is an economically important pathogen of citrus. CTV resides in the phloem of the infected plants and induces a range of disease phenotypes, including stem pitting and quick decline as well as a number of other deleterious syndromes. To uncover the biological processes underlying the poorly understood damaging symptoms of CTV, we profiled the transcriptome of sweet orange (Citrus sinensis) phloem-rich bark tissues of non-infected, mock-inoculated trees and trees singly infected with two distinct variants of CTV, T36 or T68-1. The T36 and T68-1 variants accumulated in the infected plants at similar titers. With that, young trees infected with T68-1 were markedly repressed in growth, while the growth rate of the trees infected with T36 was comparable to the mock-inoculated trees. Only a small number of differentially expressed genes (DEGs) were identified in the nearly asymptomatic T36-infected trees, whereas almost four-fold the number of DEGs were identified with the growth-restricting T68-1 infection. DEGs were validated using quantitative reverse transcription-PCR. While T36 did not induce many noteworthy changes, T68-1 altered the expression of numerous host mRNAs encoding proteins within significant biological pathways, including immunity and stress response proteins, papain-like cysteine proteases (PLCPs), cell-wall modifying enzymes, vascular development proteins and others. The transcriptomic alterations in the T68-1-infected trees, in particular, the strong and persistent increase in the expression levels of PLCPs, appear to contribute to the observed stem growth repression. On the other hand, analysis of the viral small interfering RNAs revealed that the host RNA silencing-based response to the infection by T36 and that by T68-1 was comparable, and thus, the induction of this antiviral mechanism may not contribute to the difference in the observed symptoms. The DEGs identified in this study promote our understanding of the underlying mechanisms of the yet unexplained growth repression induced by severe CTV isolates in sweet orange trees.